Magma mixing and hybridism : a preliminary study from southern Iceland - JØRGENSEN, Karl A. (1982)
The importance of magma-mixing in the generation of intermediate rock types is discussed in the light of two occurrences of mixed rocks found in the Tindfjallajökull silicic centre, S.-Iceland. The first being a minor mafic part of the large Thorsmörk ignimbrite (Jørgensen, 1980), demonstrates the formation of non-linearly derived hybrids through differential interdiffusion of elements, in connection with resorption/crystallization of phenocryst phases, demonstrated by the occurrence of abundant xenocrysts of feldspar and pyroxene and new crystallization of pyroxene and magnetite in the hybrids. The second occurrence is a mafic lava of benmoreitic composition, containing xenocrysts of acid and basic feldspars and pyroxenes in addition to unresorbed phases in equilibrium with the melt. Several other rocks show disequilibrium features which may indicate mixing of two contrasting magma types, though other rock types contain phases which may be remnants from partial melting of crustal material, as well as of fractional crystallization.